Viability of Tumpaan-strained rotifers, Brachionus rotundiformis, at different salinities - Asy'ari, Asy'ari; Kaligis, Erly; Wullur, Stenly; Rimper, Joice (AQUATIC SCIENCE & MANAGEMENT, 2014)
Title (Bahasa Indonesia): Viabilitas rotifer Brachionus rotundiformis strain tumpaan pada salinitas berbeda The purpose of the research was to analyze the viability of eggs of Tumpaan-strained rotifer, Brachionus rotundiformis, at different salinities (10 and 20 ppt). Rotifer collection was done in the area of reclamation plan and household wastewater disposal located in the coastal village of Tumpaan 1, South Minahasa Regency. At the time of sample collection, water quality parameters of the sampling site were also measured. After multiplication through clone culture in the salinity of 10 ppt and 20 ppt, the viability of the rotifer was then tested by daily observing the number of live rotifers, the number of eggs carried and the number of youngsters produced. The data were then calculated using the life table method. Results showed that water quality of the rotifer collection site is suitable for the rotifer to live. The rotifers held in 10 ppt salinity had higher survivorship and population growth (fertility rate and Ro) than those in 20 ppt salinity. This reflects that beside the quality of feed, rotifer growth is affected by salinity as well. Tujuan penelitian ini untuk menganalisis viabilitas tetasan telur dari rotifer Brachionus rotundi-formis strain Tumpaan pada salinitas berbeda (10 dan 20 ppt). Pengambilan rotifer dilakukan di suatu areal rencana reklamasi dan tempat pembuangan penelitian air limbah rumah tangga bertempat di pesisir Desa Tumpaan Satu Kabupaten Minahasa Selatan. Pada saat pengambilan hewan uji, parameter kualitas air di lokasi sampling juga diukur. Setelah diperbanyak dengan kultur klon pada salinitas 10 dan 20 ppt, rotifer kemudian diuji viabilitas dengan melakukan pengamatan setiap hari data jumlah rotifer yang hidup, jumlah telur yang dibawah dan jumlah anak yang dihasludgean. Data kemudian dihitung menggunakan metode life table.Hasil pengukuran kualitas air dari perairan tempat pengambilan rotifer termasuk layak untuk kehidupan rotifer. Rotifer yang diuji pada salinitas 10 ppt memiliki kemampuan hidup serta pertumbuhan populasi (nilai Ro dan laju fertilitas) lebih tinggi dibandingkan pada salinitas 20 ppt. Hal ini menunjukkan bahwa selain kualitas pakan, pertumbuhan rotifer juga dipengaruhi oleh salinitas.